Capacity Building Perempuan Terkait Literasi Mitigasi Bencana di Kabupaten Demak - Himmatul Ulya; Lukki Lukitawati; Yadi Suryadi; M. Fikri Amrullah (Universitas Negeri Semarang, 2023)
Demak Regency is one of the areas affected by development disasters and natural disasters in the form of floods due to loss of drainage and tidal floods. Even though they are experiencing quite serious threats, disaster mitigation measures have never been carried out by the government, and the public has not been exposed to knowledge about disaster risk management. Women have a strategic role in disaster management and can be effective agents in transferring their knowledge to the next generation. Especially to increase the skills and abilities of individuals, families, and communities in dealing with disasters to increase the number of people exposed to disaster risks. In this community service, the Loireng Village Community Welfare Empowerment Organization (PKK) was chosen as a partner, because Loireng Village experienced a serious flood disaster in early 2023. The aim of this activity is to improve disaster mitigation skills for women in Loiremg Village. This community service consists of four stages, the first stage is carried out to find out partners' needs, the second stage is coordination with the community, and the third stage is disaster risk management outreach activities regarding disaster preparedness through guidance from facilitators. The final stage is education by giving booklets to PKK members. With this outreach, it is hoped that PKK members will have disaster mitigation guidelines regarding the importance of evacuation, aid, and rescue, especially for the community itself.